Z-scheme plasmonic Ag decorated WO3/Bi2WO6 hybrids for enhanced photocatalytic abatement of chlorinated-VOCs under solar light irradiation - Zhou, H.; Wen, Z.; Liu, J.; Ke, J.; Duan, Xiaoguang; Wang, S. (Elsevier BV, 2019)
© 2018 Elsevier B.V. Ag decorated WO3/Bi2WO6hybrid heterojunction with a direct Z-scheme band structure has been synthesized by a novel method for efficient removal of gaseous chlorinated-volatile organic compounds (VOCs) under simulated sunlight irradiation. Bismuth atoms were inserted into the [WO6] layers of tungstate acid to form [Bi2O2] layers toward the formation of a Bi2WO6crystal phase, which results in Z-scheme WO3/Bi2WO6heterojunction. Ag nanoparticles (NPs) were further introduced and uniformly anchored on the surface of the WO3/Bi2WO6for improving visible-light absorption and adjusting behavior of photoinduced charge carriers in the heterostructure through surface plasmon resonance (SPR). In comparison with pristine Bi2WO6and WO3/Bi2WO6, Ag/WO3/Bi2WO6exhibits a better photocatalytic activity for removal of gaseous chlorobenzene under simulated sunlight irradiation. The conversion efficiency of 2% Ag/WO3/Bi2WO6heterojunction is 2.5 and 1.9 times higher than those of the pristine Bi2WO6and WO3/Bi2WO6samples, respectively. The improved photocatalytic activity is mainly attributed to the formation of three-component heterojunction with the Z-scheme structure and SPR effect of Ag NPs, which could not only increase absorption of visible light, but also promote the separation efficiency of photogenerated electrons and holes in the hybrids.